Letter to the editor / Uvodnik - Rebolj, Danijel (Acta Medico-Biotechnica, 2021)
The Chinese proverb says »A healthy person has a thousand wishes, a sick person only has one«. I guess there is no physician without such an experience in their daily practice. According to several surveys, health is our greatest value; however, we only begin to appreciate it, when it is no longer there. At that point, a disease appears as a negation of our health and treatments required. Medicine, scientifically dealing with treatment, comes into play. Medicine is, of course, more than just science. It comprises everything that stimulates health, cures and prevents diseases. Principally, medicine is about humanity, philanthropy and helping people not to be taken ill (prophylaxis),to recover (curative) and to suffer as little as possible (palliative). At least this is how it is supposed to be, and I believe it truly is. One expects from physicians not only to be sensible, but also good individuals, thus placing great responsibility on their hands.